2015
DOI: 10.3899/jrheum.150297
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Triamcinolone Hexacetonide versus Methylprednisolone Acetate Intraarticular Injections in Knee Osteoarthritis: A Randomized, Double-blinded, 24-week Study

Abstract: Both IA therapies are equally effective, and improvement in pain and function can be sustained for up to 24 weeks. Controlled-trials.com identifier: ISRCTN15077843.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 26 publications
1
30
0
2
Order By: Relevance
“…However, there were no differences between both corticosteroids. 62 Increased recognition of the role of synovitis in the pathogenesis of human OA makes one wonder how the stage and degree of synovitis may impact treatment results. One of the biggest contrasts when discussing IA corticosteroid use in horses compared with the human knee is the stage of synovitis usually being treated (generally acute in the horse and more mixed with considerable chronic synovitis in the human knee).…”
Section: Factors That Might Affect a Response To Intra-articular Cortmentioning
confidence: 99%
“…However, there were no differences between both corticosteroids. 62 Increased recognition of the role of synovitis in the pathogenesis of human OA makes one wonder how the stage and degree of synovitis may impact treatment results. One of the biggest contrasts when discussing IA corticosteroid use in horses compared with the human knee is the stage of synovitis usually being treated (generally acute in the horse and more mixed with considerable chronic synovitis in the human knee).…”
Section: Factors That Might Affect a Response To Intra-articular Cortmentioning
confidence: 99%
“…The use of intra-articular corticosteroid injections as an adjuvant therapy in the treatment of inflammatory arthritis 54,55 and knee and hip osteoarthritis [56][57][58][59] is well established, and it may help preserve the integrity of the joint. 60 Intra-articular corticosteroid injections generally provide short-term pain relief and functional improvement, 61,62 although there is great variability in the duration and magnitude of the clinical response. In a longitudinal cohort study, an intra-articular corticosteroid injection guided by computed tomography provided significant clinical improvement at 6 months in active sacroiliitis in patients with spondylarthropathy.…”
Section: Use Of Corticosteroids In Musculoskeletal Disorders Articulamentioning
confidence: 99%
“…The manufacturer-recommended dose for knee injections (large joint) is 40-80 mg (Summary of Product Characteristics -Depo-Medrone ® , 2014; Summary of Product Characteristics -Depo-Medrol ® , 2014). Studies on the effectiveness of MPA injections have shown clinical benefit with doses of 40 mg (Jones and Doherty, 1996;Lomonte et al, 2015;Yavuz et al, 2012) and 60 mg (Wagner et al, 2015). In studies on triamcinolone acetonide (TA), a higher dose (80 mg) showed no additional benefit compared with 40 mg (Popma et al, 2015).…”
Section: Dosementioning
confidence: 99%